Optimalisasi Tri Pusat Pendidikan dalam Meningkatkan Literasi, Inklusivitas dan Karakter Anak di Desa Narawita Kabupaten Bandung - Ririn Nuraeni; Syayidah Nuriyah; Regi Ridwan Gunawan; Gian Ahdiningtias; Kurniawan (LPPM UNINUS, 2025)
The real work activities (KKN) nusantara university in the village of narawita district of bandung, west Java province, aim to strengthen literacy, inclusive education and child character through family collaboration, school and community. Three major programs are started: bimbara (narawita study guide), inclusive educational training for teachers and kader posyandu, and the bullying seminar